Per una narratologia postumanista. Bruce Clarke, Posthuman Metamorphosis: Narrative and Systems (ENTHYMEMA International journal of literary criticism, literary theory, and philosophy of literature, 2010)
Recensiamo il libro di Bruce Clarke Posthuman Metamorphosis: Narrative and Systems, Fordham University Press, New York, 2008